IMMERSIVE AUGMENTED REALITY APPLICATIONS IN JAW AND KNEE REPLACEMENT SURGERY: ACCURACY AND PROCESSING TIME RESULTS - Salah, Shahad A.; Albabawat, Ali A.; Omer, Lamya A.; Salah, Razwan M.; Sadiq, Mohammed H. (Science Journal of University of Zakho, 2024)
In medicine and healthcare, augmented reality (AR) has been used by physicians during surgical procedures. It has proved helpful in preoperative planning and procedure navigation by allowing them to display in-depth information and visualize details in real time during surgery, prioritizing patient safety and healthcare. Due to the critical nature of surgical procedures, extreme accuracy is required when using ar technology to maintain patients’ health. A few years ago, ar faced several challenges and limitations in surgeries, such as noise in real-time images, cutting errors, navigation errors, wrong implant placement, overlay errors, navigating narrow areas, geometric accuracy limitations, image alignment, image registration, and occlusion handling. This paper reviews several recently published articles exploring ar technology usage in jaw and knee replacement surgery, focusing on identifying the newest technologies, methods, and solutions for the abovementioned limitations. Based on data collected from the published papers, the results were compared for each problem solved in each article regarding accuracy and processing time.